2001
DOI: 10.1128/jcm.39.11.4204-4207.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ehrlichia Genotype Detected in Dogs in South Africa

Abstract: DNA samples from dogs presenting with symptoms suggestive of canine ehrlichiosis, but with no morulae detected on blood smears, frequently failed to give a positive reaction with a North American Ehrlichia canis-specific PCR assay targeting the 16S rRNA gene. We suspected the presence of a pathogen genetically different from North American E. canis, and we performed experiments to test this hypothesis. DNA from one canine blood sample was subjected to PCR with primers designed to amplify Ehrlichia (Cowdria) ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…In cases of canine granulocytic ehrlichiosis (CGE) (caused by E. ewingii or A. phagocytophilum), morulae are not differentiated by optic microscopy (PREOZI and COHN, 2002). On the other hand, when dog blood samples with suggestive symptoms of ehrlichiosis, but with no morulae detected in blood smears, were submitted to molecular techniques, a negative result was obtained (ALLSOPP and ALLSOPP, 2001;DAGNONE et al, 2003). Low rickettsiemia can also lead to negative results by cytology and PCR (DU PLESSIS et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In cases of canine granulocytic ehrlichiosis (CGE) (caused by E. ewingii or A. phagocytophilum), morulae are not differentiated by optic microscopy (PREOZI and COHN, 2002). On the other hand, when dog blood samples with suggestive symptoms of ehrlichiosis, but with no morulae detected in blood smears, were submitted to molecular techniques, a negative result was obtained (ALLSOPP and ALLSOPP, 2001;DAGNONE et al, 2003). Low rickettsiemia can also lead to negative results by cytology and PCR (DU PLESSIS et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an Ehrlichia ruminantium -like sp. has been detected by PCR in domestic dogs in South Africa (Allsopp and Allsopp 2001) and the serologic cross-reactivity of E. canis and E. ruminantium has been demonstrated (Kelly et al 1994). Previous studies have identified Bartonella henselae in lions, but both serologic and molecular-based prevalence rates are low (Molia et al 2004;Pretorius et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, DNA of E. canis and DNA of a novel Ehrlichia sp. closely related to E. ruminantium have been found in the blood of dogs in South Africa (1). There is also little definitive data on infections in dogs in other parts of Africa.…”
mentioning
confidence: 99%